The Effect of Green Innovation, Green Organizational Culture, Eco-Efficiency and Collaboration on Competitive Advantage - Rosiliana, Neng Putri Asih; Dewi, R. Rosiyana (Vocational School, Universitas Sebelas Maret (UNS), Indonesia, 2023)
Currently, the increase and competition of industrial development cause natural resource depletion. It is worsened by the pollution that comes from the production process of manufacturing companies with high-profile status. This study aims to analyze the effect of Green Innovation, Green Organizational Culture, Eco-Efficiency, and Collaboration on Competitive Advantage. This study employed a quantitative approach and used secondary data. Causal research was used to establish a relationship between the variables studied and the results of the research questions. Companies listed on the Indonesia Stock Exchange with high profile status in the Consumer Cyclical, Consumer Non-Cyclical, Basic Materials, Industrials, and Healthcare sectors from 2019-2021, were used as samples and taken by purposive sampling. A total of 67 companies participated, with a total of 201 research samples that lasted for three years. This study used descriptive statistical methods, panel data regression selection tests, and hypothesis testing using Eviews 12 software. The results of the model estimation test show that the selected model, namely the Random Effect Model (REM), is the regression analysis method. This study shows that partially the independent variables Green Innovation and Eco-Efficiency as well as the control variables Firm Size and Financial Performance (ROA) have a positive and significant effect on the Competitive Advantage of High-Profile Companies from 2019 to 2021. Meanwhile, the Green Organizational Culture and Collaboration variables do not affect the Competitive Advantage of High-Profile Companies from 2019 to 2021.